Variation in translations of biblical quotations in Žemčiūga Teologiška by Simonas Vaišnoras (1600) - Kietytė, Samanta (Lietuvių kalba, 2020)
The aim of this article is to investigate the translation variations of Biblical quotations in Simonas Vaišnoras’ Žemčiūga Teologiška. This text is a translation of Adam Francisci’s theological tractate Margarita Theologica, and it was published in 1600. From the first sight, it seems that Vaišnoras tried to make his translation as similar to the original as possible. That is why, in many cases, his translation looks literal and a lot of syntactic constructions and the word order in it seem to be closer to Latin than the Lithuanian language. However, a closer look at the translations of Biblical quotations shows a different situation. In some cases, Biblical quotations are translated differently in different places of the text. Those variations include lexemes, word order, morphological features. Some of those variations are determined by the variations of the translation’s source Margarita Theologica. Another group of the variations appear because the author chose to translate not from Margarita Theologica, but from the Luther Bible. Nevertheless, more than a half of the cases (16 from 28) cannot be explained by the influence of translation sources. It shows that Simonas Vaišnoras was quite free translating this text and sometimes let himself deviate from the original. This article also focuses on the nature of variations – they are classified by the levels of language. The majority of variations are made at the lexical level (43 %), a little bit less are at the syntactic level (37 %), and the least are at the morphological level (20 %).